2017
DOI: 10.1097/igc.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Human Epididymis Protein 4 Levels in Early Stage Endometrial Cancer: A Prospective Study

Abstract: A preoperative HE4 evaluation could help stratify patients with deep invasion and/or metastatic disease and is correlated with other relevant prognostic factors to be considered to tailor an adequate surgical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…These results present similar accuracy as compared to blood derived markers reported by other research groups [30, 35, 41].…”
Section: Discussionsupporting
confidence: 90%
“…These results present similar accuracy as compared to blood derived markers reported by other research groups [30, 35, 41].…”
Section: Discussionsupporting
confidence: 90%
“…To date, the well-investigated biomarkers for EC evaluation are cancer antigen 125 (CA-125) and human epididymis protein 4 (HE4). Multiple studies have demonstrated that both CA-125 and HE4 have potential prognostic properties (9)(10)(11)(12)(13). While, in comparison to CA-125, HE4 reveals a superior diagnostic accuracy to distinguish physiological, benign, or malignant gynecological diseases (9,14).…”
Section: Introductionmentioning
confidence: 99%
“…Also the sensitivity and the specificity of CA-125 is lower for EC than OC [21]. Several studies have shown that HE4 is a novel sensitive and specific biomarker for EC [23][24][25].…”
Section: He-4 In Endometrial Cancermentioning
confidence: 96%